3D Hybrid Scaffolds Based on PEDOT:PSS/MWCNT Composites - Jayaram, Akhila K.; Pitsalidis, Charalampos; Tan, Ellasia; Moysidou, Chrysanthi-Maria; De Volder, Michael F. L.; Kim, Ji-Seon; Owens, Roisin M. (Frontiers in Chemistry, 2019)
Conducting polymer scaffolds combine the soft-porous structures of scaffolds with the electrical properties of conducting polymers. In most cases, such functional systems are developed by combining an insulating scaffold matrix with electrically conducting materials in a 3D hybrid network. However, issues arising from the poor electronic properties of such hybrid systems, hinder their application in many areas. This work reports on the design of a 3D electroactive scaffold, which is free of an insulating matrix. These 3D polymer constructs comprise of a water soluble conducting polymer (PEDOT:PSS) and multi-walled carbon nanotubes (MWCNTs). The insertion of the MWCNTs in the 3D polymer matrix directly contributes to the electron transport efﬁciency, resulting in a seven-fold decrease in resistivity values. The distribution of CNTs, as characterised by SEM and Raman spectroscopy, further define the micro- and nano-structural topography while providing active sites for protein attachment, thereby rendering the system suitable for biological/sensing applications. The resulting scaffolds, combine high porosity, mechanical stability and excellent conducting properties, thus can be suitable for a variety of applications ranging from tissue engineering and biomedical devices to (bio-) energy storage.